Penerapan Model Discovery Learning Dalam Pembelajaran Sosiologi Untuk Meningkatkan Kemampuan Berfikir Kritis Dan Hasil Belajar Siswa Di SMAN 5 Maros - Munawati Munawati; Suardi Suardi (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This classroom action research (PTK) aims to improve the critical thinking skills and learning outcomes of class XI students at SMAN 5 MAROS by applying the Discovery Learning learning model. Data was obtained based on the results of observations and tests. Data analysis was carried out using comparative descriptive techniques. The research subjects were class XI students with a total of 35 students. The results of cycle 1 research showed that students' critical thinking abilities were in the high category 4%, 28% in the medium category, 40% in the low category, and 28% in the very low category. In cycle II, the increase was shown in the critical thinking skills of students in the very high category, 32%, in the high category, 12%, in the medium category, 56%, in the low category, none and in the very low category, none. the completeness of student learning outcomes in cycle I increased in cycle II. The incomplete students consisted of 12 students, while the complete students consisted of 23 students out of 35 students in cycle I. Meanwhile, in cycle II, all students completed, namely 35 students.